Long‐term lesser prairie‐chicken nest ecology in response to grassland management. Issue 3 (13th February 2016) - Fritts, Sarah R.; Grisham, Blake A.; Haukos, David A.; Boal, Clint W.; Patten, Michael A.; Wolfe, Don H.; Dixon, Charles E.; Cox, Robert D.; Heck, Willard R.
ABSTRACT: Long‐term population and range declines from habitat loss and fragmentation caused the lesser prairie‐chicken ( Tympanuchus pallidicinctus ) to be a species of concern throughout its range. Current lesser prairie‐chicken range in New Mexico and Texas is partially restricted to sand shinnery oak ( Quercus havardii ; hereafter shinnery oak) prairies, on which cattle grazing is the main socioeconomic driver for private landowners. Cattle producers within shinnery oak prairies often focus land management on shrub eradication using the herbicide tebuthiuron to promote grass production for forage; however, herbicide application alone, and in combination with grazing, may affect nest site selection and nest survival of lesser prairie‐chickens through the reduction of shinnery oak and native grasses. We used a controlled, paired, completely randomized design study to assess the influence of grazing and tebuthiuron application and their combined use on nest site selection and nest survival from 2001 to 2010 in Roosevelt County, New Mexico, USA at 2 spatial scales (i.e., treatment and microhabitat) in 4 treatments: tebuthiuron with grazing, tebuthiuron without grazing, no tebuthiuron with grazing, and a control of no tebuthiuron and no grazing. Grazing treatment was a short‐duration system in which plots were grazed once during the dormant season and once during the growing season. Stocking rate was calculated each season based on measured forage production and applied to remove ≤25% of available herbaceous material per season. At the treatment scale, we compared nest site selection among treatments using 1‐way χ 2 tests and nest survival among treatments using a priori candidate nest survival models in Program MARK. At the microhabitat scale, we identified important habitat predictors of nest site selection and nest survival using logistic regression and a priori candidate nest survival models in Program MARK, respectively. Females typically used treatments as expected and we did not detect trends in selection. Nest survival did not differ among treatments. At the microhabitat scale, nest sites had less bare ground ( P  = 0.001) and greater angles of obstruction ( P  ≤ 0.001) compared to random sites. There was a high degree of model selection uncertainty among our candidate models at the microhabitat scale and survival estimates were similar among habitat covariates. Results suggest a tebuthiuron application rate of 0.60 kg/ha, short‐duration grazing, and a combination of these management techniques were not detrimental to lesser prairie‐chicken nest site selection or nest survival. However, intensified management that increases bare ground or reduces overhead cover may negatively affect lesser prairie‐chicken nesting habitat and nest survival. © 2016 The Wildlife Society.